Dada a função g(x)= 2x²-6x-4 , calcule g(3) ???
Soluções para a tarefa
Respondido por
4
Boa noite Bianquinha!
Solução!
![g(x)=2 x^{2} -6x-4 g(x)=2 x^{2} -6x-4](https://tex.z-dn.net/?f=g%28x%29%3D2+x%5E%7B2%7D+-6x-4)
Agora é só substituir 3 no lugar de x na função.
![g(3)=2 (3)^{2} -6(3)-4 g(3)=2 (3)^{2} -6(3)-4](https://tex.z-dn.net/?f=g%283%29%3D2+%283%29%5E%7B2%7D+-6%283%29-4)
![g(x)=2 (9) -6(3)-4 g(x)=2 (9) -6(3)-4](https://tex.z-dn.net/?f=g%28x%29%3D2+%289%29+-6%283%29-4)
![g(3)=(18-18)-4 g(3)=(18-18)-4](https://tex.z-dn.net/?f=g%283%29%3D%2818-18%29-4)
![g(3)=0-4 g(3)=0-4](https://tex.z-dn.net/?f=g%283%29%3D0-4)
![g(3)=-4 g(3)=-4](https://tex.z-dn.net/?f=g%283%29%3D-4)
Boa noite!
Bons estudos!
Solução!
Agora é só substituir 3 no lugar de x na função.
Boa noite!
Bons estudos!
bianqinhagolld:
muuuito obriagad!!
Perguntas interessantes
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Sociologia,
1 ano atrás